Beyond the log frame: a new tool for examining health and peacebuildin g initiatives - Grove, Natalie J.; Zwi, Anthony B. (Development in Practice, 2008)
How do we move from identifying ethical principles to enhancing develo pment practice? How can donors and NGOs move beyond the reporting of t echnical outputs to explore less tangible aspects of their health proj ects: contributions to rebuilding trust, promoting social cohesion, an d enhancing good governance at community level? This article considers these questions in relation to health and peace-building activities i n conflicted settings. It describes difficulties facing practitioners and donors seeking to undertake health and peace work, in particular f ocusing on the lack of appropriate tools for screening, monitoring, an d evaluating projects. It critiques the logical framework, a tool comm only used in project planning, monitoring, and evaluation, and conside rs it alongside a new tool, the Health and Peace Building Filter, whic h has been designed to reflect on health programming in fragile or con flicted settings. The authors argue that such tools can help to move u s beyond focusing on inputs and outputs to examining processes, relati onships, and the indirect consequences of aid programmes.